Strategi Keuangan Perguruan Tinggi Negeri dalam Transisi Menuju Badan Layanan Umum: Studi Kasus di Universitas Bangka Belitung - Topan Persada; Lela Nurlaela Wati; Ira Geraldina (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
In response to the challenges of globalization and the need to increase financial flexibility, many state universities (PTN) in Indonesia have chosen to transition to becoming public service agencies (BLU). This step is expected to provide greater autonomy in financial and resource management while increasing the competitiveness of institutions. This study aims to analyze PTN’s financial management strategy for transitioning to BLU status using a case study at Universitas Bangka Belitung (UBB). The research approach used is qualitative descriptive with the SWOT analysis method to evaluate internal and external factors influencing the transition process. Data were collected through in-depth interviews, documentation studies, and observations of financial policies and practices at UBB. The research results revealed that the transition to BLU offers significant flexibility in financial management, allowing UBB to be more independent in using non-tax state revenue (PNBP). This directly contributes to improving operational efficiency and institutional competitiveness. However, several major challenges must be addressed, such as limited infrastructure, lack of highly qualified teaching staff, and competition with other state universities with BLU or PTN-BH status. This study also found that the greatest opportunities for Universitas Bangka Belitung (UBB) lie in optimizing assets and expanding industrial cooperation, primarily through the Kampus Merdeka program. In conclusion, UBB can leverage its BLU status to enhance the institution’s competitiveness by implementing more flexible financial management, but it requires a clear strategy to tackle internal challenges. Recommendations include increasing the teaching staff’s capacity, optimizing assets, and developing strategic partnerships with industry.